EFL Students ‘Perception on the Use of Google Translate in Translation Class - Nugraeni, Anita Hafila; Ahmad, Zuhad (Institut Agama Islam Negeri Palopo, 2024)
This research aims to analyze students' perceptions on the use of Google Translate in Translation class, which can provide new insights into how technology can affect students' learning experience and to identify the common problems encountered by students in using Google Translate. The researcher used a descriptive qualitative research approach. The researcher used 35 university students from the English Education Department using a questionnaire. Additionally, to delve deeper into the common problems encountered by students when using Google Translate, the researcher conducted semi-structured interviews with five students. Based on the data analysis, EFL students have a positive perception of the use of Google Translate in translation classes, finding it easy to use and helpful. Moreover, the common problems encountered when using Google Translate in translation classes include errors in sentences, the need for carefulness, and EFL students' continued reliance on Google Translate to translate quickly and complete their tasks. This poses a serious challenge for students in developing their translation skills independently.